Business plans handbook : a compilation of business plans developed by individuals throughout North America. Volume 15 - 4 0 16; Pearce, Lynn M.; 5 (Detroit, MI : Gale Cengage Learning, 2009)
Actual business plans compiled by, and aimed at, entrepreneurs seeking funding for small businesses. Presents sample plans taken from businesses in the manufacturing, retail and service industries which serve as examples of how to approach, structure and compose business plans.
Air brushing services --;Art easel manufacturer --;Bicycle shop --;Comedy club --;DVD kiosk rental business --;Energy consultant --;Environmentally-friendly greenhouse --;Furniture resale shop --;Furniture restoration company --;Healthcare marketing agency --;Low-cost home decorating service --;Music store --;Natural gas home filling station provider --;Photography studio --;Plus-sized children's clothing store --;Real estate brokerage --;Real estate renovation and resale --;Rental defibrillator service --;Windmill distributor --;Yoga studio.
ISSN 1084-4473.
Mode of Access for E-Book: World Wide Web.
Keywords: 2 -- 0; 6; Planning;Planning;Information services -- Small business;Business planning;Small business;New business enterprises;Entrepreneurship -- 20 -- Handbooks, manuals, etc.;Handbooks, manuals, etc.;Directories.;Handbooks, manuals, etc.;Handbooks, manuals, etc; 20; 2